ARNI Pre-Operative Use and Vasoplegic Syndrome in Patients Undergoing Heart Transplantation or Left Ventricular Assist Device Surgery - Lamis Haider; Elisabeth Hugon-Vallet; Jean Philippe Constantin; Zakaria Riad; Laurent Sebbag; Nathan Mewton (Medical Sciences, 2021)
Background: Vasoplegic syndrome after orthotopic heart transplantation (OHT) or left ventricular assist device (LVAD) implantation is a rare but highly lethal syndrome with complex etiologies. The objective of this study was to assess if the preoperative use of sacubitril-valsartan combination is associated with an increased vasoplegic syndrome (VS) frequency after OHT or LVAD implantation and its relationship with 30-day mortality. Methods: A retrospective review of perioperative data, between January 2016 and December 2017, from 73 consecutive OHT and LVAD surgery adult patients at our institution was performed. VS was defined as normal cardiac output with persistent low systemic resistance requiring a norepinephrine intravenous perfusion > 0.5 µg/kg/min and the absence of sepsis or hemorrhagic shock within 48 h after surgery. Patients were all followed-up for adverse events and all-cause mortality at 30 days. Results: In our cohort of 73 patients (median age 51.7 years, 65% male patients), 25 (34%) patients developed VS. Twenty-two (30.1%) patients were on ARNI at the time of surgery, 31 (42.5%) were on other RAS blockers, 12 (16.4%) were on norepinephrine and 8 (11%) had no pre-operative drug. The pre-operative use of any vasoactive agent, was not significantly associated with VS (OR = 1.36; IC95% [0.78; 2.35]; p = 0.38). The pre-operative use of an ARNI compared to all other groups was not significantly associated with VS (OR = 2.0; IC95% [0.71; 5.62]; p = 0.19). The pre-operative use of an ARNI compared to other RAS blockers was also not significantly associated with VS (OR = 1.25; IC95% [0.37; 4.26]; p = 0.72). At 30 days, 18 (24.7%) patients had died. The pre-operative treatment with ARNI, or other RAS inhibitors was associated with a significantly lower rate of death compared to the absence of treatment (HR = 0.11; IC95% [0.02; 0.55]; p = 0.009 for ARNI and HR = 0.20; IC95% [0.06; 0.69]; p = 0.011 for other RASi). Conclusions: Preoperative use of sacubitril-valsartan was not significantly associated with development of vasoplegic syndrome in patients undergoing OHT or LVAD surgery. Furthermore, our data suggests a significant 30-day survival benefit with efficient renin-angiotensin blockade before surgery.